Fallacia fawensis sp. nov., a new brackish water diatom (Bacillariophyceae) from Southern Iraq - Al-Handal, Adil Y.; Al-Shaheen, Maitham A.; Al-Saedy, Rehab N.; Wulff, Angela (Phytotaxa, 2022)
The diatom genus Fallacia includes species having a conopeum which is a perforated thin sheath of silica lying along the apical axis on the external valve face and a hyaline lateral area in the internal valve face. In surveying the benthic diatoms of Basra, a new small brackish water species, Fallacia fawensis was found associated with fine-grained substrata on the western bank of Shatt Al–Arab River, Southern Iraq. This epipelic species is described based on light and scanning electron microscopy and characterized by having a porous conopeum covering the area between raphe sterna and mantle, narrow elongated marginal striae, and a structure similar to lateral hyaline areas in the valve internal side. The terminal raphe endings on the external valve face, below valve apex, the raphe sternum inner margins come close to each other, blocking raphe canal but leaving a lacuna-like thin groove for connection with the deflected upper part of the open raphe canal. These features separated this species from allied taxa of the genus and also from closely related genera, Pseudofallacia and Germaniella. Notes on the ecology and distribution of the new species as well as the associated diatom taxa are provided.